Noting as Learning: Its Significance for Teaching and Learning Japanese in Volunteer Language Classrooms for Migrants (Sains Humanika, 2017)
This paper discusses problems in volunteer Japanese classrooms as a field of teaching foreign language for special purposes, which is to enhance migrant learners in the neighbourhood to participate in the host society through the target language. The data on which the discussion is based was collected from a case study conducted in a volunteer Japanese classroom in eastern Japan. From the point of view of â€œnotingâ€ in the Language Management Theory (LMT; cf. NeustupnÃ½ 1985, 1994; Jernudd and NeustupnÃ½ 1987), the findings suggest that although all the learners in the classroom intend to stay in Japan permanently, they appear to be reluctant to interact with local Japanese and to expand their Japanese social network due to the inability to note deviations from norms underlying in Japanese speech situations. In the second half of the paper, I raise an example of teaching materials to illustrate that noting as learning can be enhanced through systematic classroom activities. It is suggested that the ability to become sensitive about possible problems when interacting with local Japanese people can help foreigners in the neighbourhood to be more prepared and thus more confident to use the target language in real life.Â Â
Keywords: Migrant Japanese education; noting; language for special purposes